Crude fiber improvement with multigrain chip with coconut flour - Castor, Myra B
Crude fiber improvement of the multigrain chip made from wheat, oats and rice was done in this study. It was achieved by determining maximum level of all-purpose flour and coconut flour that can be substituted to cake flour without significantly altering the chips' texture. Maximum level of substitution was chosen based on similarity of hardness histograms of chips made from the different levels of all-purpose flour and coconut flour with 100% cake flour. A modified shortometer was devised for these tests. Verification of the chosen level of substitution was done through sensory evaluation using the descriptive method, while proximate analysis of the finished product was conducted using approved AOAC methods. From four levels of substitution of all-purpose flour (5%, 10%, 15% and 20%) the maximum level of substitution allowable without significantly altering the chips' texture was 25% for all-purpose flour and 10% for coconut flour. Proximate composition of the finished product (chips with 10% coconut flour) was as follows: 0.82% crude fiber; 17.35% crude fat; 9.0% crude protein; 65.32% total available carbohydrate; 3.09% moisture and 4.42% ash. Under the conditions of the study the crude fiber content of the multigrain chop control made from 100% wheat flour was 0.45% while that of the chips made with 10% substitution of coconut residue flour to wheat flour was 0.82%.